Using inter‐institutional practice variation to understand the risks and benefits of routine labour induction at 41+0 weeks. (14th July 2014) - Hutcheon, JA; Harper, S; Strumpf, EC; Lee, L; Marquette, G
<x xml:space="preserve">Abstract</x> Objective To evaluate the risks and benefits of routine labour induction at 41+0 weeks' gestation for mother and newborn. Design Population‐based retrospective cohort study of inter‐institutional variation in labour induction practices for women at or beyond 41+0 weeks' gestation. Population Women in British Columbia, Canada, who remained pregnant ≥41+0 weeks and delivered at one of the province's 42 hospitals with >50 annual deliveries, 2008–2012 (n = 14 627). Methods The proportion of women remaining pregnant a week or more past the expected delivery date who were induced at 41+0 or 41+1 weeks' gestation for an indication of 'post‐dates' was calculated for each institution. We used instrumental variable analysis (using the institutional rate of labour induction at 41+0 weeks as the instrument) to estimate the effect of labour induction on maternal and neonatal health outcomes. Main outcome measures Caesarean delivery, instrumental delivery, post‐partum haemorrhage, 3rd or 4th degree lacerations, macrosomia, neonatal intensive care unit admission, and 5‐minute Apgar score <7. Results Institutional rates of labour induction at 41+0 weeks ranged from 14.3 to 46%. Institutions with higher (≥30%) and average (20–29.9%) induction rates did not have significantly different rates of caesarean delivery, instrumental delivery, or other maternal or neonatal outcomes than institutions with lower induction rates (<20%). Instrumental variable analyses also demonstrated no significantly increased (or decreased) risk of caesarean delivery (0.69 excess cases per 100 pregnancies [95% CI −10.1, 11.5]), instrumental delivery (8.9 per 100 [95% CI −2.3, 20.2]), or other maternal or neonatal outcomes in women who were induced (versus not induced). Conclusions Within the current range of clinical practice, there was no evidence that differential use of routine induction at 41+0 weeks affected maternal or neonatal health outcomes.